The peasant's rescue from the cadre? An institutional analysis of China's rural tax and fee reform - Christian Göbel (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2006)
Applying a historical institutionalist perspective, this paper examines the genesis, implementation process and impact of the recent Rural Tax and Fee Reform (RTFR) in China. It is posited that the RTFR represents a serious, although inconsistent, attempt to shift the balance of central-local relations toward the centre via stricter regulation of county and subcounty politics. It is further argued that this attempt to restructure the polity is not matched by the adjustment of the policy process. As the former is pushed towards significant change in the realm of central-local relations, the latter remains unchanged. More concretely, the centre has taken a results-oriented view of central-local relations, a path that has begun with the implementation of a planned economy, and not occupied itself with the formal regulation of the policy processes that are supposed to create these results. At the same time, local politics is path-dependent in the sense that Reform and Opening gave local governments the incentive to create informal institutions to pursue their own economic and policy goals. With central and county politics running along these two divergent paths, trying to change the polity in a way that benefits only one of the players becomes impossible if the centre is not prepared to apply massive coercion. Not only do such tactics fail to reduce social tension, but they also produce additional political tension. These elements do not bode well for sustained burden reduction.
Keywords: 330; Rural Tax and Fee Reform; peasant burden; Anhui province; historical institutionalism; path dependence; central-local relations; Ländlicher Raum; Gebühr; Steuerreform; Institutioneller Wandel; China